Corrosion-resistant high-conductivity nickel-coated copper core and preparation method thereof

By adding corrosion-resistant coatings of components such as epoxy resin emulsion, composite filler and polytetrafluoroethylene emulsion to the nickel-covered copper core, combined with a multi-layer protective structure of nickel-coated layer and composite filler, the problem of corrosion in extreme environments is solved, and higher corrosion resistance and service life are achieved.

CN119889759AActive Publication Date: 2025-04-25SHANGHAI KE-FA PRECISE ALLOY MATERIAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510068818.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Nickel-covered copper materials may still corrode in corrosive media such as strong acids and alkalis in extreme environments, affecting the service life and reliability of the product.

Method used

A nickel-clad copper core composed of a copper core, a nickel-plated layer and a corrosion-resistant coating is used. The coating consists of epoxy resin emulsion, composite filler, polytetrafluoroethylene emulsion and other components. The binding force between diatomaceous earth and molybdenum oxide is enhanced through specific treatment methods, and glass flakes and silane coupling agent are introduced to form a multi-layer protective structure.

Benefits of technology

It significantly enhances the corrosion resistance and mechanical strength of nickel-clad copper core, extends the service life of the product, and remains stable in various corrosive environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant high-conductivity nickel-coated copper core and a preparation method thereof, and belongs to the technical field of nickel-coated copper cores. The surface of the copper core is uniformly coated with a compact nickel layer, the nickel layer is further coated with a corrosion-resistant coating, the corrosion-resistant coating is obtained by coating and curing a corrosion-resistant coating, and the formula of the corrosion-resistant coating comprises the following components in parts by weight: 1-10 parts of a corrosion-resistant additive, 1-10 parts of a corrosion-resistant additive, 1-10 parts of a corrosion-resistant additive and 1-10 parts of a corrosion-resistant additive. The coating is prepared from 70-90 parts of epoxy resin emulsion, 10-20 parts of composite filler, 5-10 parts of polytetrafluoroethylene emulsion, 3-5 parts of curing agent and 1-2 parts of polydimethylsiloxane. According to the nickel-coated copper core obtained by the invention, the corrosion resistance and the impact resistance of the nickel-coated copper core are also remarkably improved while high conductivity is maintained. The preparation method disclosed by the invention is simple in process and easy for industrial production, and the obtained product is stable in performance and suitable for being applied in various special environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nickel-clad copper cores and relates to a corrosion-resistant and highly conductive nickel-clad copper core and a preparation method thereof. Background Art

[0002] As a metal with excellent electrical conductivity, copper is widely used in electrical and electronic fields, but its corrosion resistance and weldability are relatively poor. Especially in harsh environments, the performance of copper materials decays rapidly, resulting in a shortened product life. In traditional applications, steel ladle copper core materials are widely used due to their good electrical conductivity and mechanical strength, but with the development of modern industry, especially in some special environments, the corrosion resistance of steel ladle copper core materials can no longer meet actual needs, which limits the further expansion of its application range. Nickel materials are known for their excellent corrosion resistance and weldability, but their relatively weak electrical conductivity limits their application in situations where high conductivity is required.

[0003] Therefore, coating the surface of the copper core with a layer of nickel can not only retain the excellent electrical conductivity of copper, but also significantly improve the corrosion resistance and weldability of the material. This nickel-clad copper composite material has broad application prospects in the fields of electrical connections, communication equipment, aerospace, etc. However, the corrosion resistance of nickel-clad copper materials still needs to be improved. Especially in some extreme environments, such as corrosive media such as strong acids and alkalis, even if nickel coating technology is used, corrosion may still occur, affecting the service life and reliability of the product. Therefore, how to further improve the corrosion resistance of nickel-clad copper materials has become an urgent problem to be solved. Summary of the invention

[0004] The object of the present invention is to provide a corrosion-resistant and highly conductive nickel-clad copper core and a preparation method thereof, which maintains the high conductivity of the copper core and has the characteristics of excellent corrosion resistance and good impact resistance.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A corrosion-resistant and highly conductive nickel-clad copper core, comprising a copper core, a nickel-plated layer and a corrosion-resistant coating from the inside to the outside.

[0007] The corrosion-resistant coating is obtained by coating and curing the corrosion-resistant coating. The formula of the corrosion-resistant coating is as follows: in parts by weight, 70 to 90 parts of epoxy resin emulsion, 10 to 20 parts of composite filler, 5 to 10 parts of polytetrafluoroethylene emulsion, 3 to 5 parts of curing agent, and 1 to 2 parts of polydimethylsiloxane.

[0008] Wherein, the preparation method of the composite filler is as follows:

[0009] S1-1: 20 to 30 parts of diatomaceous earth are placed in 100 parts of sodium hydroxide solution, ultrasonicated at 60 to 80°C for 20 to 40 minutes, then washed with deionized water, and then dried in a vacuum drying oven for 6 to 8 hours to obtain powder A;

[0010] S1-2: 15-25 parts of powder A are added to 50-60 parts of deionized water, stirred for 30 minutes, then 3-5 parts of ammonium molybdate are added, and stirring is continued for 2 hours. The deionized water is removed by rotary evaporation at 60°C, and then the powder is calcined in a muffle furnace to obtain powder B;

[0011] S1-3: 10-20 parts of powder B are added to 30-40 parts of phytic acid solution, ultrasonicated at 40-50°C for 10 min, then stirred at 550-650 r / min at room temperature for 1-2 h, washed with deionized water, and then freeze-dried in a freeze dryer for 8-12 h to obtain powder C;

[0012] S1-4: Powder C and glass flakes are mixed in a mass ratio of (1-2):1, and the mixture is placed in a ball mill for 40-60 min at a ball milling speed of 150 r / min. Then, silane coupling agent KH570 is added, and the speed is maintained while continuing the ball milling for 1-3 h to obtain the composite filler.

[0013] As a preferred technical solution of the present invention, the preparation method of the corrosion-resistant coating is as follows:

[0014] The epoxy resin emulsion, the composite filler and the polytetrafluoroethylene emulsion are mixed according to the formula ratio, stirred at a speed of 700 to 800 r / min for 30 to 50 minutes, then polydimethylsiloxane is added, the speed is maintained and stirring is continued for 20 minutes, and finally a curing agent is added, and stirring is continued at a speed of 800 to 900 r / min for 5 to 10 minutes to obtain the corrosion-resistant coating.

[0015] As a preferred technical solution of the present invention, the curing agent is an amine curing agent.

[0016] As a preferred technical solution of the present invention, the concentration of the sodium hydroxide solution in S1-1 is 0.2M.

[0017] As a preferred technical solution of the present invention, the calcination temperature in S1-2 is 600-800°C, and the calcination time is 1-2h.

[0018] As a preferred technical solution of the present invention, the mass fraction of the phytic acid solution in S1-3 is 10-20%.

[0019] As a preferred technical solution of the present invention, the added amount of the silane coupling agent KH570 in S1-4 is 3% of the total weight of the powder C and the glass flakes.

[0020] A method for preparing a corrosion-resistant and highly conductive nickel-clad copper core, the specific steps of the preparation method are as follows:

[0021] S8-1: soak the copper core in a degreasing solution, ultrasonicate at 60-80°C for 5-15 min, wash the copper core with 80-90°C deionized water, then place it in a 0.2M hydrochloric acid solution for pickling for 5-15 s, wash it with 20-40°C deionized water, and then place it in a 60°C vacuum drying oven for drying for 6-8 h to obtain a pretreated copper core;

[0022] S8-2: Place the pretreated copper core in the electrolyte for electroplating at a temperature of 45-55°C, a time of 8-10 min, a voltage of 3-4 V, and a current density of 1-2 A / dm 2 , obtaining a nickel-plated layer;

[0023] S8-3: Apply a corrosion-resistant coating on the surface of the nickel-plated layer and cure it at 75 to 85° C. for 1 to 2 hours to obtain the corrosion-resistant and highly conductive nickel-clad copper core.

[0024] As a preferred technical solution of the present invention, the composition of the degreasing liquid in S8-1 is 20-30 g / L sodium carbonate, 40-60 g / L sodium phosphate, 1-3 g / L sodium dodecyl sulfate, and the solvent is deionized water.

[0025] As a preferred technical solution of the present invention, the composition of the electrolyte in S8-2 is 230-250 g / L nickel sulfate, 4-6 g / L sodium chloride, 20-30 g / L boric acid, 5-10 g / L sodium citrate, and the solvent is deionized water.

[0026] Copper is a metal with high conductivity, which can effectively transmit current and ensure the high conductivity of nickel-clad copper core. Nickel plating on the surface of copper core significantly enhances the corrosion resistance of copper core. The nickel plating layer can prevent the corrosive medium from directly contacting the copper core, and the metal nickel itself also has good corrosion resistance.

[0027] As the main component of the coating, epoxy resin emulsion has excellent waterproof, moisture-proof and anti-corrosion properties. It can effectively isolate the entry of oxygen or water vapor and reduce the oxidation corrosion rate of the surface of the nickel-clad copper core. Epoxy resin emulsion has good adhesion and can adhere tightly to the nickel-plated layer to ensure the stability and durability of the coating, which helps prevent the coating from falling off or being damaged during transportation, installation, maintenance, etc. The coating formed after the epoxy resin emulsion is cured has high mechanical strength and can withstand certain mechanical properties such as shear, bending, and impact.

[0028] In the preparation of composite fillers, diatomite is treated with sodium hydroxide. Sodium hydroxide can effectively react with the silicate structure on the surface of diatomite, remove impurities on the surface of diatomite, and promote the generation and exposure of hydroxyl functional groups on the surface of diatomite, increasing the active sites on its surface. During the roasting process, ammonium molybdate decomposes at high temperatures to generate molybdenum oxides. These oxides have high chemical stability and activity, and can form chemical bonds with functional groups such as hydroxyl groups on the surface of diatomite, which not only enhances the bonding force between diatomite and molybdenum oxide, but also makes the entire composite structure more stable and durable. At the same time, since molybdenum oxide itself has high hardness and wear resistance, the mechanical properties of the coating can be further improved. In addition, the porous cage structure of diatomaceous earth is conducive to the adsorption and storage of molybdenum oxide and other substances, significantly increasing the content of effective ingredients in the coating; the pores of diatomaceous earth form a complex network in the coating, and when the corrosive medium tries to penetrate into the interior of the coating, these pore structures act as a physical barrier, increasing the diffusion path and difficulty of the corrosive medium; when the coating is eroded by the corrosive medium, molybdenum oxide can be released from the pores of the diatomaceous earth, reacting with the corrosive medium or forming a protective layer.

[0029] The carboxyl group in phytic acid can react with metal ions to form a stable chelate, thereby improving the chemical stability of the coating. After the reaction between phytic acid and metal ions, a dense protective layer can be formed on the surface of the coating, which can further block the contact between the corrosive medium and the coating substrate and enhance the corrosion resistance of the coating.

[0030] Glass flakes are an inorganic material with a flaky structure. Adding glass flakes to composite fillers can enhance the toughness of the coating. The flaky structure of glass flakes can form a "maze effect" in the coating, increasing the diffusion path of the corrosive medium. At the same time, the glass flakes themselves have high toughness and can improve the impact resistance and cracking resistance of the coating. When glass flakes are combined with ingredients such as phytic acid, diatomaceous earth and molybdenum oxide, they can form a multi-layer protective structure in the coating, which can more effectively block the penetration of corrosive media and improve the corrosion resistance of the coating. In addition, the addition of glass flakes can also improve the appearance of the coating, making it smoother.

[0031] Silane coupling agent KH570 can act as a bridge to tightly combine the composite filler with the organic resin, thereby improving the interfacial bonding strength and overall stability of the coating. The addition of silane coupling agent KH570 can also improve the hydrophobicity of the coating surface, reduce the erosion of water on the coating, and thus improve the water resistance and corrosion resistance of the coating.

[0032] Polytetrafluoroethylene emulsion has good resistance to strong acids, strong alkalis, oxidants and most solvents, and has excellent chemical stability and weather resistance. Adding polytetrafluoroethylene emulsion to the coating formula can make the finished coating remain stable in various corrosive environments, further extending the service life of the coating and substrate.

[0033] Beneficial effects of the present invention:

[0034] Through the design of the nickel plating layer, the corrosion resistance of the copper core is significantly enhanced while maintaining its high conductivity. As the main component of the coating, the epoxy resin emulsion not only has excellent waterproof, moisture-proof and corrosion-resistant properties, but also adheres tightly to the nickel plating layer, ensuring the stability and durability of the coating. In the preparation of the composite filler, the binding force between diatomaceous earth and molybdenum oxide is enhanced through specific treatment, and the corrosion resistance of the coating is improved; the addition of phytic acid further enhances the chemical stability and corrosion resistance of the coating; the introduction of glass flakes enhances the toughness of the coating, forming a multi-layer protective structure, which more effectively blocks the penetration of corrosive media; the silane coupling agent KH570 improves the interfacial bonding and overall stability of the coating; the addition of polytetrafluoroethylene emulsion enables the coating to remain stable in various corrosive environments, extending the service life of the nickel-clad copper core. DETAILED DESCRIPTION

[0035] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0036] Example 1

[0037] A corrosion-resistant and highly conductive nickel-clad copper core, comprising a copper core, a nickel-plated layer and a corrosion-resistant coating from the inside to the outside.

[0038] The corrosion-resistant coating is obtained by curing the corrosion-resistant coating. The formula 1 of the corrosion-resistant coating is as follows: in parts by weight, 80 parts of epoxy resin emulsion, 15 parts of composite filler, 7 parts of polytetrafluoroethylene emulsion, 4 parts of ethylenediamine, and 1.5 parts of polydimethylsiloxane.

[0039] Wherein, the preparation method of the composite filler is as follows:

[0040] S1-1: 25 parts of diatomaceous earth were placed in 100 parts of 0.2M sodium hydroxide solution, ultrasonicated at 70°C for 30 minutes, then washed with deionized water, and then dried in a vacuum drying oven for 7 hours to obtain powder A;

[0041] S1-2: 20 parts of powder A were added to 55 parts of deionized water, stirred for 30 minutes, then 4 parts of ammonium molybdate were added, and the stirring was continued for 2 hours. The deionized water was removed by rotary evaporation at 60°C, and then the mixture was calcined in a muffle furnace at a temperature of 700°C for 1.5 hours to obtain powder B;

[0042] S1-3: 15 parts of powder B were added to 35 parts of 15% phytic acid solution, ultrasonicated at 45°C for 10 min, then stirred at 600 r / min at room temperature for 1.5 h, washed with deionized water, and freeze-dried in a freeze dryer for 10 h to obtain powder C;

[0043] S1-4: Mix powder C and glass flakes in a mass ratio of 1.5:1, place them in a ball mill and ball mill for 50 minutes at a ball mill speed of 150 r / min, then add silane coupling agent KH570 in an amount of 3% of the total weight of powder C and glass flakes, maintain the speed and continue ball milling for 2 hours to obtain the composite filler.

[0044] The preparation method of the corrosion-resistant coating is as follows:

[0045] The epoxy resin emulsion, composite filler and polytetrafluoroethylene emulsion were mixed according to the proportion of formula 1, stirred at a speed of 750 r / min for 40 minutes, then polydimethylsiloxane was added, and the stirring was continued for 20 minutes while maintaining the speed, and finally ethylenediamine was added, and stirred at a speed of 850 r / min for 8 minutes to obtain the corrosion-resistant coating.

[0046] A method for preparing a corrosion-resistant and highly conductive nickel-clad copper core, the specific steps of the preparation method are as follows:

[0047] S8-1: The copper core is immersed in a degreasing liquid, the composition of which is 25 g / L sodium carbonate, 50 g / L sodium phosphate, and 2 g / L sodium dodecyl sulfate, and the solvent is deionized water, and the copper core is ultrasonically treated at 70°C for 10 min, and then washed with 85°C deionized water, and then placed in a 0.2M hydrochloric acid solution for pickling for 10 s, and then washed with 30°C deionized water, and then placed in a 60°C vacuum drying oven for 7 h to obtain a pretreated copper core;

[0048] S8-2: The pretreated copper core is placed in an electrolyte for electroplating. The electrolyte composition is 240g / L nickel sulfate, 5g / L sodium chloride, 25g / L boric acid, and 7g / L sodium citrate. The solvent is deionized water. The electroplating temperature is 50°C, the electroplating time is 9min, the voltage is 3.5V, and the current density is 1.5A / dm 2 , obtaining a nickel-plated layer;

[0049] S8-3: Apply a corrosion-resistant coating on the surface of the nickel-plated layer and cure it at 80° C. for 1.5 hours to obtain the corrosion-resistant and highly conductive nickel-clad copper core.

[0050] Example 2

[0051] A corrosion-resistant and highly conductive nickel-clad copper core, comprising a copper core, a nickel-plated layer and a corrosion-resistant coating from the inside to the outside.

[0052] The corrosion-resistant coating is obtained by curing the corrosion-resistant coating. The formula 2 of the corrosion-resistant coating is as follows: in parts by weight, 70 parts of epoxy resin emulsion, 10 parts of composite filler, 5 parts of polytetrafluoroethylene emulsion, 3 parts of ethylenediamine, and 1 part of polydimethylsiloxane.

[0053] Wherein, the preparation method of the composite filler is as follows:

[0054] S1-1: 20 parts of diatomaceous earth were placed in 100 parts of 0.2M sodium hydroxide solution, ultrasonicated at 60°C for 20 minutes, then washed with deionized water, and then dried in a vacuum drying oven for 6 hours to obtain powder A;

[0055] S1-2: 15 parts of powder A were added to 50 parts of deionized water, stirred for 30 minutes, and then 3 parts of ammonium molybdate were added, and the stirring was continued for 2 hours. The deionized water was removed by rotary evaporation at 60°C, and then the mixture was calcined in a muffle furnace at a temperature of 600°C for 1 hour to obtain powder B;

[0056] S1-3: 10 parts of powder B were added to 30 parts of 10% phytic acid solution, ultrasonicated at 40°C for 10 min, then stirred at room temperature at a speed of 550 r / min for 1 h, washed with deionized water, and then freeze-dried in a freeze dryer for 8 h to obtain powder C;

[0057] S1-4: Mix powder C and glass flakes in a mass ratio of 1:1, place them in a ball mill and ball mill for 40 minutes at a ball mill speed of 150 r / min, then add silane coupling agent KH570 in an amount of 3% of the total weight of powder C and glass flakes, maintain the speed and continue ball milling for 1 hour to obtain the composite filler.

[0058] The preparation method of the corrosion-resistant coating is as follows:

[0059] The epoxy resin emulsion, composite filler and polytetrafluoroethylene emulsion were mixed according to the proportion of formula 2, stirred at a speed of 700 r / min for 30 minutes, then polydimethylsiloxane was added, and the stirring was continued for 20 minutes while maintaining the speed, and finally ethylenediamine was added, and stirred at a speed of 800 r / min for 5 minutes to obtain the corrosion-resistant coating.

[0060] A method for preparing a corrosion-resistant and highly conductive nickel-clad copper core, the specific steps of the preparation method are as follows:

[0061] S8-1: The copper core is immersed in a degreasing liquid, the composition of which is 20 g / L sodium carbonate, 40 g / L sodium phosphate, and 1 g / L sodium dodecyl sulfate, and the solvent is deionized water, and the copper core is ultrasonically treated at 60°C for 5 min, and then washed with 80°C deionized water, and then placed in a 0.2M hydrochloric acid solution for pickling for 5 s, and then washed with 20°C deionized water, and then placed in a 60°C vacuum drying oven for 6 h to obtain a pretreated copper core;

[0062] S8-2: The pretreated copper core is placed in an electrolyte for electroplating. The electrolyte composition is 230g / L nickel sulfate, 4g / L sodium chloride, 20g / L boric acid, 5g / L sodium citrate, the solvent is deionized water, the electroplating temperature is 45°C, the electroplating time is 8min, the voltage is 3V, and the current density is 1A / dm 2 , obtaining a nickel-plated layer;

[0063] S8-3: Apply a corrosion-resistant coating on the surface of the nickel-plated layer and cure it at 75° C. for 2 hours to obtain the corrosion-resistant and highly conductive nickel-clad copper core.

[0064] Example 3

[0065] A corrosion-resistant and highly conductive nickel-clad copper core, comprising a copper core, a nickel-plated layer and a corrosion-resistant coating from the inside to the outside.

[0066] The corrosion-resistant coating is obtained by coating and curing the corrosion-resistant coating. The formula 3 of the corrosion-resistant coating is as follows: in parts by weight, 90 parts of epoxy resin emulsion, 20 parts of composite filler, 10 parts of polytetrafluoroethylene emulsion, 5 parts of ethylenediamine, and 2 parts of polydimethylsiloxane.

[0067] Wherein, the preparation method of the composite filler is as follows:

[0068] S1-1: 30 parts of diatomaceous earth were placed in 100 parts of 0.2 M sodium hydroxide solution, ultrasonicated at 80°C for 40 min, then washed with deionized water, and then dried in a vacuum drying oven for 8 h to obtain powder A;

[0069] S1-2: 25 parts of powder A were added to 60 parts of deionized water, stirred for 30 minutes, and then 5 parts of ammonium molybdate were added, and the stirring was continued for 2 hours. The deionized water was removed by rotary evaporation at 60°C, and then the mixture was calcined in a muffle furnace at a temperature of 800°C for 2 hours to obtain powder B;

[0070] S1-3: 20 parts of powder B were added to 40 parts of phytic acid solution with a mass fraction of 20%, and ultrasonicated at 50°C for 10 minutes, then stirred at room temperature at a speed of 650 r / min for 2 hours, washed with deionized water, and then freeze-dried in a freeze dryer for 12 hours to obtain powder C;

[0071] S1-4: Mix powder C and glass flakes in a mass ratio of 2:1, place them in a ball mill and ball mill for 60 minutes at a ball mill speed of 150 r / min, then add silane coupling agent KH570, the addition amount of silane coupling agent KH570 is 3% of the total weight of powder C and glass flakes, maintain the speed and continue ball milling for 3 hours to obtain the composite filler.

[0072] The preparation method of the corrosion-resistant coating is as follows:

[0073] The epoxy resin emulsion, composite filler and polytetrafluoroethylene emulsion were mixed according to the proportion of formula 3, stirred at a speed of 800 r / min for 50 minutes, then polydimethylsiloxane was added, and the stirring was continued for 20 minutes while maintaining the speed, and finally ethylenediamine was added, and stirred at a speed of 900 r / min for 10 minutes to obtain the corrosion-resistant coating.

[0074] A method for preparing a corrosion-resistant and highly conductive nickel-clad copper core, the specific steps of the preparation method are as follows:

[0075] S8-1: The copper core is immersed in a degreasing liquid, the composition of which is 30 g / L sodium carbonate, 60 g / L sodium phosphate, and 3 g / L sodium dodecyl sulfate, and the solvent is deionized water, and the copper core is ultrasonically treated at 80°C for 15 min, and then washed with deionized water at 90°C, and then placed in a 0.2M hydrochloric acid solution for pickling for 15 s, and then washed with deionized water at 40°C, and then placed in a vacuum drying oven at 60°C for 8 h to obtain a pretreated copper core;

[0076] S8-2: The pretreated copper core is placed in an electrolyte for electroplating. The electrolyte composition is 250g / L nickel sulfate, 6g / L sodium chloride, 30g / L boric acid, 10g / L sodium citrate, the solvent is deionized water, the electroplating temperature is 55°C, the electroplating time is 10min, the voltage is 4V, and the current density is 2A / dm 2 , obtaining a nickel-plated layer;

[0077] S8-3: Apply a corrosion-resistant coating on the surface of the nickel-plated layer and cure it at 85° C. for 2 hours to obtain the corrosion-resistant and highly conductive nickel-clad copper core.

[0078] Comparative Example 1

[0079] Ammonium molybdate was not added during the preparation of the composite filler, and the remaining steps were the same as those in Example 1.

[0080] Comparative Example 2

[0081] No phytic acid solution was added during the preparation of the composite filler, and the remaining steps were the same as those in Example 1.

[0082] Comparative Example 3

[0083] No glass flakes are added in the preparation of the composite filler, and the remaining steps are consistent with Example 1.

[0084] Comparative Example 4

[0085] No polytetrafluoroethylene emulsion is added in the preparation of the corrosion-resistant coating, and the remaining steps are consistent with Example 1.

[0086] Comparative Example 5

[0087] The nickel plating step is omitted, and the remaining steps are the same as those in Example 1.

[0088] The resistivity of Examples 1 to 3 was tested with reference to GB / T 1424-1996 standard, and the experimental data are summarized in the following table.

[0089] Resistivity(Ω.m) Example 1 0.062538 Example 2 0.062680 Example 3 0.062595

[0090] The corrosion resistance of Examples 1 to 3 and Comparative Examples 1 to 5 was tested with reference to GB / T 10125-2021 standard, and the experimental data are summarized in the following table.

[0091] Corrosion resistance (h) Example 1 2200 Example 2 2100 Example 3 2150 Comparative Example 1 1900 Comparative Example 2 1800 Comparative Example 3 1700 Comparative Example 4 1850 Comparative Example 5 2000

[0092] The corrosion-resistant and highly conductive nickel-clad copper cores prepared in Examples 1 to 3 and Comparative Example 3 were tested for impact resistance with reference to IEC 60068-2-27 standard. The experimental data are summarized in the following table.

[0093] Impact resistance(h) Example 1 5100 Example 2 4950 Example 3 5030 Comparative Example 3 4520

[0094] It can be seen from the data of the embodiments and comparative examples that the nickel-clad copper core prepared in the present invention maintains the high electrical conductivity of the copper core and has excellent corrosion resistance and impact resistance.

[0095] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A corrosion-resistant and highly conductive nickel-clad copper core, characterized in that: The corrosion-resistant and highly conductive nickel-clad copper core comprises a copper core, a nickel-plated layer and a corrosion-resistant coating from the inside to the outside. The corrosion-resistant coating is obtained by coating and curing the corrosion-resistant coating. The formula of the corrosion-resistant coating is as follows: in parts by weight, 70 to 90 parts of epoxy resin emulsion, 10 to 20 parts of composite filler, 5 to 10 parts of polytetrafluoroethylene emulsion, 3 to 5 parts of curing agent, and 1 to 2 parts of polydimethylsiloxane. Wherein, the preparation method of the composite filler is as follows: S1-1: 20 to 30 parts of diatomaceous earth are placed in 100 parts of sodium hydroxide solution, ultrasonicated at 60 to 80°C for 20 to 40 minutes, then washed with deionized water, and then dried in a vacuum drying oven for 6 to 8 hours to obtain powder A; S1-2: 15-25 parts of powder A are added to 50-60 parts of deionized water, stirred for 30 minutes, then 3-5 parts of ammonium molybdate are added, and stirring is continued for 2 hours. The deionized water is removed by rotary evaporation at 60°C, and then the powder is calcined in a muffle furnace to obtain powder B; S1-3: 10-20 parts of powder B are added to 30-40 parts of phytic acid solution, ultrasonicated at 40-50°C for 10 min, then stirred at 550-650 r / min at room temperature for 1-2 h, washed with deionized water, and then freeze-dried in a freeze dryer for 8-12 h to obtain powder C; S1-4: Powder C and glass flakes are mixed in a mass ratio of (1-2):1, and the mixture is placed in a ball mill for 40-60 min at a ball milling speed of 150 r / min. Then, silane coupling agent KH570 is added, and the speed is maintained while continuing the ball milling for 1-3 h to obtain the composite filler.

2. The corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The preparation method of the corrosion-resistant coating is as follows: The epoxy resin emulsion, the composite filler and the polytetrafluoroethylene emulsion are mixed according to the formula ratio, stirred at a speed of 700 to 800 r / min for 30 to 50 minutes, then polydimethylsiloxane is added, the speed is maintained and stirring is continued for 20 minutes, and finally a curing agent is added, and stirring is continued at a speed of 800 to 900 r / min for 5 to 10 minutes to obtain the corrosion-resistant coating.

3. The corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The curing agent is an amine curing agent.

4. The corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in S1-1 is 0.2M.

5. The corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: In the S1-2, the calcination temperature is 600-800° C., and the calcination time is 1-2 hours.

6. The corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The mass fraction of the phytic acid solution in S1-3 is 10-20%.

7. The corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The added amount of the silane coupling agent KH570 in S1-4 is 3% of the total weight of the powder C and the glass flakes.

8. A method for preparing the corrosion-resistant and highly conductive nickel-clad copper core according to any one of claims 1 to 7, characterized in that: The specific steps of the preparation method are as follows: S8-1: soak the copper core in a degreasing solution, ultrasonicate at 60-80°C for 5-15 min, wash the copper core with 80-90°C deionized water, then place it in a 0.2M hydrochloric acid solution for pickling for 5-15 s, wash it with 20-40°C deionized water, and then place it in a 60°C vacuum drying oven for drying for 6-8 h to obtain a pretreated copper core; S8-2: Place the pretreated copper core in the electrolyte for electroplating at a temperature of 45-55°C, a time of 8-10 min, a voltage of 3-4 V, and a current density of 1-2 A / dm 2 , obtaining a nickel-plated layer; S8-3: Apply a corrosion-resistant coating on the surface of the nickel-plated layer and cure it at 75 to 85° C. for 1 to 2 hours to obtain the corrosion-resistant and highly conductive nickel-clad copper core.

9. The method for preparing a corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The composition of the degreasing liquid in S8-1 is 20-30 g / L sodium carbonate, 40-60 g / L sodium phosphate, 1-3 g / L sodium dodecyl sulfate, and the solvent is deionized water.

10. The method for preparing a corrosion-resistant and highly conductive nickel-clad copper core according to claim 1, characterized in that: The electrolyte in S8-2 is composed of 230-250 g / L nickel sulfate, 4-6 g / L sodium chloride, 20-30 g / L boric acid, and 5-10 g / L sodium citrate, and the solvent is deionized water.

Citation Information

Patent Citations

  • Corrosion-resistant copper wire

    CN105261405A

  • Anti-corrosion seawater cable, production method and detection method thereof

    CN109344359A

  • Paint

    CN109423156A

  • Production process of oil-resistant, wear-resistant and corrosion-resistant sealing ring coating for oil field

    CN112608666A

  • Crosslinked polyethylene insulated corrosion-resistant power cable and production process thereof

    CN116759148A